2023
DOI: 10.1093/molbev/msad206
|View full text |Cite
|
Sign up to set email alerts
|

Selection on Visual Opsin Genes in Diurnal Neotropical Frogs and Loss of the SWS2 Opsin in Poison Frogs

Yin Chen Wan,
María José Navarrete Méndez,
Lauren A O'Connell
et al.

Abstract: Amphibians are ideal for studying visual system evolution because their biphasic (aquatic and terrestrial) life history and ecological diversity expose them to a broad range of visual conditions. Here, we evaluate signatures of selection on visual opsin genes across Neotropical anurans and focus on three diurnal clades that are well-known for the concurrence of conspicuous colors and chemical defense (i.e., aposematism): poison frogs (Dendrobatidae), Harlequin toads (Bufonidae: Atelopus), and pumpkin toadlets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 119 publications
0
3
1
Order By: Relevance
“…There is strong evidence for the loss of SWS2 in dendrobatids, and corresponding loss of the blue-sensitive rods where SWS2 is typically expressed in frogs. We did not find SWS2 expressed in the dendrobatid eye transcriptomes, and another study was also unable to recover SWS2 from dendrobatid bait-capture data or an eye transcriptome ( Wan et al 2023 ); however, in the two dendrobatid genomes, we found short fragments that are likely pseudogene remnants of SWS2 , based on phylogenetic analysis. Furthermore, retinal microspectrophotometry (MSP) to estimate photoreceptor absorbance spectra did not detect blue-sensitive rods in the three dendrobatids examined here or the species examined previously ( Siddiqi et al 2004 ).…”
Section: Discussioncontrasting
confidence: 70%
“…There is strong evidence for the loss of SWS2 in dendrobatids, and corresponding loss of the blue-sensitive rods where SWS2 is typically expressed in frogs. We did not find SWS2 expressed in the dendrobatid eye transcriptomes, and another study was also unable to recover SWS2 from dendrobatid bait-capture data or an eye transcriptome ( Wan et al 2023 ); however, in the two dendrobatid genomes, we found short fragments that are likely pseudogene remnants of SWS2 , based on phylogenetic analysis. Furthermore, retinal microspectrophotometry (MSP) to estimate photoreceptor absorbance spectra did not detect blue-sensitive rods in the three dendrobatids examined here or the species examined previously ( Siddiqi et al 2004 ).…”
Section: Discussioncontrasting
confidence: 70%
“…From left to right: an ultrametric tree showing phylogenetic relationships inferred previously [55] among sampled species with the three defended poison frog clades highlighted in purple, the undefended clades in dark gray, and non-dendrobatids in light gray (Bufonidae: Amazophrynella siona and Atelopus aff. spurrelli ; Leptodactylidae: Lithodytes lineatus ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, data are not directly comparable, and they could not be included in Figure 3. Phylogenies were subsetted from [59] using ape v5.7.1 [94] and phytools v1.9.16 [95]. Any compounds known to co-elute with other compounds were unable to be identified, so we averaged their quantities across the co-eluting compounds.…”
Section: (D) Analysesmentioning
confidence: 99%
“…Given that amphibians display a wide spectrum of ecological traits (habitat, rhythmic activity, reproductive mode, behaviour and colour patterns [26][27][28]), they represent an interesting group for understanding how properties of the visual system differ among diverse photic environments. In addition, recent studies began to explore different aspects of visual ecology in relation to both morphological and spectral variations, particularly in anuran eyes [29][30][31][32][33][34][35][36][37]. Still, knowledge of the taxonomic distribution of the ODs in anurans remains sparse owing to the patchiness of the studied species across the anuran phylogenetic diversity, hindering any evaluation of its evolution and relationship with visual ecology in the group [9].…”
Section: Introductionmentioning
confidence: 99%